Quercetin treatment protects the Achilles tendons of rats from oxidative stress induced by hyperglycemia - Tomoya Yoshikawa; Yutaka Mifune; Atsuyuki Inui; Hanako Nishimoto; Kohei Yamaura; Shintaro Mukohara; Issei Shinohara; Ryosuke Kuroda (BMC Musculoskeletal Disorders, 2022)
Abstract Background Quercetin, a flavonoid abundantly in vegetables and fruits, exerts antioxidant and anti-inflammatory effects. We investigated the protective effects of quercetin against oxidative stress in the Achilles tendons of diabetic rats. Methods Cells were collected from the Achilles tendons of Sprague–Dawley rats and cultured under four conditions: regular glucose (RG) without quercetin (Quer-), RG with quercetin (Quer +), high-glucose (HG) Quer-, and HG Quer + . The expression of genes related to NADPH oxidase (NOX) and inflammation, reactive oxygen species accumulation, and apoptosis rates was analyzed. Additionally, diabetic rats were divided into two groups and subjected to quercetin (group Q) or no quercetin (group C) treatment. Histological evaluation and expression analysis of relevant genes in the Achilles tendon were performed. Results In rat tendon-derived cells, the expression of Nox1, Nox4, and Il6; reactive oxygen species accumulation; and apoptosis rates were significantly decreased by quercetin treatment in the HG group. The collagen fiber arrangement was significantly disorganized in the diabetic rat Achilles tendons in group C compared with that in group Q. The mRNA and protein expression levels of NOX1 and NOX4 were significantly decreased upon quercetin treatment. Furthermore, the expression of Il6, type III collagen, Mmp2, and Timp2 was significantly decreased, whereas that of type I collagen was significantly increased in group Q compared with that in group C. Conclusions Quercetin treatment decreases NOX expression and thus exerts antioxidant and anti-inflammatory effects in the Achilles tendons of diabetic rats. Quercetin treatment may be effective against diabetic tendinopathy.